2020
DOI: 10.1101/2020.10.12.336941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postnatal fluoxetine treatment alters perineuronal net formation and maintenance in the hippocampus

Abstract: Elevation of serotonin via postnatal fluoxetine (PNFlx) treatment during critical temporal windows is hypothesized to perturb the development of limbic circuits thus establishing a substratum for persistent disruption of mood-related behavior. We examined the impact of PNFlx treatment on the formation and maintenance of perineuronal nets (PNNs), extracellular matrix (ECM) structures that deposit primarily around inhibitory interneurons, and mark the closure of critical period plasticity. PNFlx treatment evoked… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…In two separate studies (Ohira et al, 2013;Guirado et al, 2014), FLX treated mice showed decreased PNN density and PV+ neurons in both mPFC and in hippocampus compared to vehicle. In concurrence with these findings, Mukhopadhyay et al, 2021 found a decrease in CA1 and CA3 hippocampal PNNs following FLX treatment in Sprague Dawley rats (Mukhopadhyay et al, 2021). Moreover, Ohira et al, 2019 found reduction of DG and CA3 hippocampal PNN density and PV+ interneurons in FLX treated marmosets (Ohira et al, 2019).…”
Section: Therapeutic Manipulation Of Pnnsmentioning
confidence: 77%
“…In two separate studies (Ohira et al, 2013;Guirado et al, 2014), FLX treated mice showed decreased PNN density and PV+ neurons in both mPFC and in hippocampus compared to vehicle. In concurrence with these findings, Mukhopadhyay et al, 2021 found a decrease in CA1 and CA3 hippocampal PNNs following FLX treatment in Sprague Dawley rats (Mukhopadhyay et al, 2021). Moreover, Ohira et al, 2019 found reduction of DG and CA3 hippocampal PNN density and PV+ interneurons in FLX treated marmosets (Ohira et al, 2019).…”
Section: Therapeutic Manipulation Of Pnnsmentioning
confidence: 77%